(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2018)
Based on the various agro-edaphic and agro-climatic characteristics, the suitability of maize cultivation during winter season has been determined in Cox’s Bazaar Sadar Upazila. For this purpose, under the existing climate conditions, considered agro-edaphic factors of various geomorphic units are soil permeability, effective soil depth, available soil moisture, soil reaction (pH), soil salinity, slope etc. Long-term climate attributes of the study area were used to determine the overall climate suitability classes, and the combined land suitability classes for maize (rabi) cultivation have been determined through the adjustment of the agro-edaphic and agro-climatic suitability criteria. Thus, recognized combined land suitability classes for maize (rabi) cultivation in the present study area are ‘highly suitable’, ‘suitable’, and ‘moderately suitable’. A total of 896 hectares land has been found as ‘highly suitable’ for maize cultivation in Cox’s Bazaar Sadar Upazila while approximately 4403 and 11,000 hectares have been identified as ‘suitable’ and ‘moderately suitable’, respectively. Asiat. Soc. Bangladesh, Sci. 44(1): 35-51, June 2018